KARAKTERISTIK PATAH DAN KETAHANAN LELAH BESI COR MALLEABLE - M Dzaky Hafidz; Hendri Chandra (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Malleable cast iron is one of the cast irons that has excellent forging properties. Malleable cast iron is the result of heat treatment of white cast iron, so that cementite is decomposed to form graphite in the form of rosettes. Malleable cast iron is often used for tooling and on railway components. Testing to determine the fatigue limit of malleable cast iron is very important so that it can find out the maximum fatigue load that malleable cast iron can receive. Fatigue testing was carried out with variations in loading angles of 1o, 2o, 3o, 4o and 5o. From the tests carried out, the fatigue limit of malleable cast iron is below a voltage of 100.4 MPa. Metallographic testing is also carried out to determine the microstructure in malleable cast iron. The microstructure formed in the specimen is in the form of graphite in the form of a rosette and there is a ferrite phase, so the malleable cast iron tested is malleable matrix ferritic cast iron. Fault surfaces in specimens were also observed through visual observation and scanning electron microscopy (SEM). Through visual observations on the surface of the fault, beachmark are seen, in specimens given a loading angle of 1o has a wider area of beachmark compared to other loading angles. This is because the smaller the loading angle, the smaller the voltage so that the crack propagation area will be wider. SEM observations indicate that the fracture that occurred was a transgranular fracture.